Influence Application of Learning Models Problem Based Learning (PBL) Against Results Study Mathematics Student Class VII SMP Negeri 1 Pangkur - Chintia Inka; Budi Sasomo; Anwas Mashuri (International Journal of Sustainability in Research, 2023)
This research aims to determine the effect of the Problem Based learning model Learning (PBL) on student learning outcomes in Mathematics class VII SMP Negeri 1 Pangkur . This research is experimental research. Where is the population of This research consisted of 7 class VII students of SMP Negeri 1 Pangkur. Meanwhile, the sample from this research was an experimental group from class VII F with PBL model totaling 2 8 students and the Control Class group from class VII G which totaling 2 8 students. The data collection technique used in this research is observation , test And documentation . From the test carried out at the last meeting, a Significant value was obtained test "t" 0.01 which means it is smaller than the significance level of 0.05 (0.01 < 0.05) so that the hypothesis nil is rejected and the alternative hypothesis is accepted. Based on the results of data analysis, it can be concluded that the mathematics learning outcomes of students who use the Problem Based Learning (PBL) model experienced better improvement than students who did not use the model Problem Based Learning (PBL).